HIV Disclosure and Quality of Life in People Living with HIV/AIDS in Yogyakarta - Tutur Irfantoro; Dwi Kartika Rukmi (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Victory Plus Foundation is a Non-Government Organization that helps the population directly affected by HIV/AIDS in Yogyakarta. Status disclosure’s research on People Living with HIV/AIDS (PLWHA) in Victory Plus Foundation is scarce. Even though the status disclosure is one of HIV spreading prevention, it has two-sided effects, both negative and positive, so its result can affect the quality of life despite PLWHA having tried to find a support system. Therefore, it is essential to know how the quality of life of PLWHA has opened up their status.Purpose: This study aimed to determine the relationship between HIV status disclosure and the quality of life of PLWHA in the Victory Plus Foundation, Yogyakarta.Method: This descriptive-analytic correlation study with a cross-sectional approach was conducted in June-July 2019 on 68 PLWHA at the Victory Plus Foundation. Purposively, samples were asked to fill out a disclosure questionnaire and WHOQOL-BREF. Univariate data presented in descriptions and Chi-Square tested bivariate data.Result: Most of the HIV status disclosure of PLWHA in the Victory Plus foundation was classified into a moderate category (77.9%) and low quality of life (64 %). The bivariate test result found a significant relationship between the HIV status disclosures with the quality of life in general (p = 0.001) with a moderate relationship closeness (r=0.403).Conclusion: Consequently, there is a relationship between the HIV status disclosures with the quality of life of PLWHA in the Victory Plus Foundation in Yogyakarta.